Effect of Thermal Treatment on Textural Properties of Natural Montmorillonite - Alsawalha, Murad (Asian Journal of Chemistry, 2018)
This paper presents the effect of heating time over natural Jordan Diatomite. The sample was selected for this study from the Azraq area, which is approximately 110 km northeast of Amman. Natural diatomite was heated in a programmable furnace from room temperature to T = 150 °C with a heating rate 10 °C/min without any further purification or acid treatment. The heating process was at various holding times (i.e. 6, 12, 18 and 24 h, respectively). Samples for each individual holding period was then characterized for determining specific surface area, pore size and pore volume as well as XRD patterns. Results indicated that the surface areas increased after 2 h of heating hold time, while a slight increase in the pore size and pore volume appeared after 24 h. The increase surface area was not changed after 5 h of holding heating time. Furthermore, the presence of peaks intensity strongly depends on the heat holding time; the longer holding heat time the higher is the peak intensity (T = 150 °C).